Role of the distal hydrogen-bonding network in regulating oxygen affinity in the truncated hemoglobin III from campylobacter jejuni - Arroyo Mañez, Pau (2011)
Oxygen affinity in heme-containing proteins is determined by a number of factors, such as the nature and conformation of the distal residues that stabilize the heme bound-oxygen via hydrogen-bonding interactions. The truncated hemoglobin III from Campylobacter jejuni (Ctb) contains three potential hydrogen-bond donors in the distal site: TyrB10, TrpG8, and HisE7. Previous studies suggested that Ctb exhibits an extremely slow oxygen dissociation rate due to an interlaced hydrogen-bonding network involving the three distal residues. Here we have studied the structural and kinetic properties of the G8WF mutant of Ctb and employed state-of-the-art computer simulation methods to investigate the properties of the O2 adduct of the G8 WF mutant, with respect to those of the wild-type protein and the previously studied E7HL and/or B10YF mutants. Our data indicate that the unique oxygen binding properties of Ctb are determined by the interplay of hydrogen-bonding interactions between the heme-bound ligand and the surrounding TyrB10, TrpG8, and HisE7 residues. © 2011 American Chemical Society.